Prognosis impact of perineural invasion in advanced stage oral squamous cell carcinoma - Araújo, Winícius Arildo Ferreira [UNESP] (2022)
Despite recent research showing low survival in cancer patients who had perineural invasion (PNI), little is known about the strength of the PNI related to oral squamous cell carcinoma (OSCC) survival and in relation to its clinicopathological variables. The specific objectives of the study were to measure the impact of the PNI on the survival of oral SCC, as well as the correlation between the clinicopathological characteristics of the patient diagnosed with OSCC of the mouth with the PNI in surgically treated patients. A retrospective study was carried out involving 101 patients who underwent surgical treatment with or without the association of adjuvant therapy between the years 1994 and 2016. All variables were entered simultaneously in the cox model for each survival model and in the cross-tabulation to evaluate the relationship between the PNI and the OSCC by mouth variables. Statistical significance for the study was established at a P value of less than 0.05. The PNI variable of interest proved to be a predictor of overall survival (HR, 3.38; 95% CI, 0.139-0.624; P = 0.004) and disease-specific survival (HR, 2.95; 95% CI 0.137-0.810; P =0.019). The PNI also showed a relationship with treatment (P = 0.011) in the correlation analysis. Perineural invasion was considered an independent variable in the specific and overall survival of patients with OSCC. Other factors related to the sensitivity of the assessment of the perineural invasion pattern in OSCC of the mouth still remain unknown.